Knee muscle strength, balance and functional independence in persons with stroke - Fernandes, Beatriz (2011)
Purpose: to investigate the relationship between knee muscle strength, balance and functional independence within the first month after stroke. Relevance: cerebral vascular disease is one of the main causes of morbidity, disability and mortality in developed countries. Problems with movement control are frequent after stroke. Lower limb weakness and impaired balance are common problems that are related with the risk of falls and are likely to interfere with the ability to perform daily life activities. Physiotherapy intervention usually starts early after stroke and addresses impairments related to movement and posture in order to improve motor recovery and restore function.